1980
DOI: 10.1002/chin.198030243
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: UNSATURATED CARBONYL‐CONTAINING COMPOUNDS. XXVIII. CYCLOADDITION OF ORGANIC AZIDES TO α‐ACETYLENE KETONES AND ACIDS

Abstract: Cycloadditionen der Azide (II) an die Acetylene (I) in siedendem Methanol (oder DMSO, Dioxan, CC14, Diethylether, Toluol) liefern Gemische der isomeren Triazole (III) und (IV) (angegeben sind die Gemischausbeuten).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Proton NMR spectroscopy (CD 3 OD) indicated that only a single regioisomer 13 was generated with a high chemical shift value (δ H 9.11 ppm) for the C-5 aromatic proton. Assignment of the structure to the 1,4disubstituted regioisomer 13 is consistent with the preferred mode of azide addition to acetylenic ketones as demonstrated by Vereshchagin et al 17 This regiochemistry also accounts for the 1 H NMR spectrum of 13 in which the phenyl substituent interacts with the triazole ring splitting the ortho protons with respect to the meta-para protons. A singlet would have been more likely expected if the phenyl substituent were in the more sterically hindered position adjacent to the carbonyl group, 18 i.e.…”
Section: Scheme 3 Reagents and Conditionssupporting
confidence: 84%
See 2 more Smart Citations
“…Proton NMR spectroscopy (CD 3 OD) indicated that only a single regioisomer 13 was generated with a high chemical shift value (δ H 9.11 ppm) for the C-5 aromatic proton. Assignment of the structure to the 1,4disubstituted regioisomer 13 is consistent with the preferred mode of azide addition to acetylenic ketones as demonstrated by Vereshchagin et al 17 This regiochemistry also accounts for the 1 H NMR spectrum of 13 in which the phenyl substituent interacts with the triazole ring splitting the ortho protons with respect to the meta-para protons. A singlet would have been more likely expected if the phenyl substituent were in the more sterically hindered position adjacent to the carbonyl group, 18 i.e.…”
Section: Scheme 3 Reagents and Conditionssupporting
confidence: 84%
“…Furthermore, it had been shown that reaction of azides with alkynyl ketones had led to exclusive addition at the acetylene. 17 Thus reaction of 4 with phenyl azide was carried out in refluxing diethyl ether 17 to generate the triazol-4-yl, protected amino acid 13, in high yield (91%) (Scheme 5). Proton NMR spectroscopy (CD 3 OD) indicated that only a single regioisomer 13 was generated with a high chemical shift value (δ H 9.11 ppm) for the C-5 aromatic proton.…”
Section: Scheme 3 Reagents and Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous report used the general synthetic scheme for producing Au MPCs having multiple functionalities with dipolar cycloaddition shown in Scheme 1 [9]. The yields of the uncatalyzed conversion of azide to triazole were lower on the Au nanoparticles' surfaces than previously reported for reactions in solution or on Au electrodes [16,[21][22][23]. However, later experimentation revealed that the I 2 decomposition and subsequent NMR analysis underestimated the reaction yields.…”
Section: Introductionmentioning
confidence: 79%